Development--At What Price? - Masri, Rania (Arab Studies Quarterly)
Discusses the environmental management in Lebanon. Examples of environmental legislation; Why most laws regarding the environment were not implemented; Impact of urbanization on arable lands; Quality of drinking water in Lebanon; Use of asbestos fiber in infrastructural development.